Information technology for supply chain innovation: a mediated covariance modeling based on dynamic capabilities theory - Singhry, Hassan Barau; Abd Rahman, Azmawani; Ng, Siew Imm (2015)
Information technology is an important supply chain innovation typology that enhances the integration of people, processes and technology. Although there is large body of literature on information technology, supply chain capabilities and supply chain performance, empirical studies on how supply chain innovation capabilities relates with information technology and supply chain performance is unknown. To cover this important research gap, the study proposed hypotheses of mediation effect of supply chain innovation capabilities between information technology and supply chain performance of manufacturing companies of Africa’s largest economy. The study followed post-positivism epistemology based on the ontology of critical realism. A cross-section of 280 top managers of manufacturing companies were examined based on cluster and stratified random sampling. A four-stage regression analysis in two models were performed to test the proposed hypotheses using structural equation modeling (SPSS IBM Amos 22.0). Result in model 1 found a significant relationship between information technology and supply chain performance. The findings in model 2 suggested that the X→M and M→Y regression paths were both significant. The initial positive and significant relationship between information technology and supply chain performance became non-significant with the introduction of supply chain innovation capability as mediator variable. Therefore, it is concluded that supply chain innovation capability is a full mediator between information technology and supply chain performance.